PENINGKATAN AKTIVITAS DAN HASIL BELAJAR IPA MELALUI MODEL PEMBELAJARAN TEAM ASSISTED INDIVIDUALIZATION (TAI) PADA SISWA KELAS VI SD NEGERI BAWANG 1 PAKIS MAGELANG - APRILINA SETYOWATI (ELEMENTARY: Jurnal Inovasi Pendidikan Dasar, 2023)
This research aims to improve science learning activities and outcomes through the team assisted individualization (TAI) learning model for class VI students at SD Negeri Bawang 1 Pakis Magelang. This research is classroom action research with the implementation of Team Assisted Individualization. Classroom action research was carried out in the odd semester of the 2022/2023 academic year. The subjects of this research were 26 students consisting of 16 female students and 10 male students. The types of data collection techniques used by researchers in this research are tests, observation and documentation. Data analysis uses quantitative techniques. From the research results it can be concluded that an increase in the percentage of student learning activities occurred from cycle I to cycle II. In cycle I, the average student learning activity was only 53.25%, then in cycle II it increased by 23.25% to 76.50% with very high achievement criteria. This increase means that students' learning activities have met the learning activity success indicators of at least 75%. This shows that the Team Assisted Individualization (TAI) learning model can increase student learning activities. The learning process using the Team Assisted Individualization (TAI) learning model can improve science learning outcomes for class VI students at SDN Bawang 1 Pakis on the theme of Entrepreneurship with magnetic material. The average class score in cycle I was 72.50, then in cycle II it increased to 82.31. Meanwhile, classical learning completeness in cycle I was only 46.15%, then in cycle II it increased to 100%. This achievement has met the success indicators of a minimum average score of 75 and the success indicators of classical completion of at least 75%. This proves that the Team Assisted Individualization (TAI) learning model has proven effective in improving student learning outcomes. ABSTRAKPenelitian ini bertujuan untuk meningkatkan aktivitas dan hasil belajar ipa melalui model pembelajaran team assisted individualization (TAI) pada siswa kelas VI SD Negeri Bawang 1 Pakis Magelang. Penelitian ini merupakan penelitian tindakan kelas dengan penerapan Team Assisted Individualization. Penelitian tindakan kelas dilaksanakan pada semester ganjil tahun pelajaran 2022/2023. Sebagai subyek penelitian ini adalah siswa 26 yang terdiri dari 16 siswa putri dan 10 siswa putra. Jenis teknik pengumpulan data yang digunakan oleh peneliti pada penelitian ini adalah tes, observasi, dan dokumentasi. Analisis data menggunakan teknik kuantitatif. Dari hasil penelitian dapat disimpulkan bahwa peningkatan persentase aktivitas belajar siswa terjadi dari siklus I ke siklus II. Pada siklus I rata-rata keaktifan belajar siswa hanya sebesar 53,25% kemudian pada siklus II meningkat 23,25% menjadi 76,50% dengan kriteria ketercapain sangat tinggi. Dengan peningkatan ini berarti perolehan aktivitas belajar siswa telah memenuhi indikator keberhasilan aktivitas belajar minimal 75%. Hal ini menunjukkan bahwa model Pembelajaran Team Assisted Individualization (TAI) dapat meningkatkan aktivitas belajar siswa. Proses pembelajaran dengan menggunakan model pembelajaran Team Assisted Individualization (TAI) dapat meningkatkan hasil belajar IPA siswa kelas VI SDN Bawang 1 Pakis pada tema Wirausaha materi magnet. Perolehan nilai rata-rata kelas pada siklus I sebesar 72,50 kemudian pada siklus II meningkat menjadi 82,31. Sedangkan ketuntasan belajar klasikal pada siklus I hanya sebesar 46,15%, kemudian pada siklus II meningkat menjadi 100%. Perolehan ini sudah memenuhi indikator keberhasilan minimal nilai rata-rata 75 dan indikator keberhasilan ketuntasan klasikal minimal 75%. Hal ini membuktikan bahwa model Pembelajaran Team Assisted Individualization (TAI) terbukti efektif meningkatkan hasil belajar siswa.